Antimicrobial potential of plastic films incorporated with sage extract on chicken meat - Aziman, Nurain; Jawaid, Mohammad; Abdul Mutalib, Noor Azira; Yusof, Noor Liyana; A. H., Nadrah; U. K., Nazatul; V. V., Tverezovskiy; O. A., Tverezovskaya; H., Fouad; R. M., Braganca; P. W., Baker; S., Selbie; et al. (Multidisciplinary Digital Publishing Institute, 2021)
The function of packaging is crucial in the maintenance of fresh meat product quality. This study aimed to assess the efficiency of six films added with coatings 2379L/220 and 2379L/221 (containing sage extracts) to inhibit Salmonella typhimurium, Staphylococcus aureus, and Escherichia coli, which showed that two of the six films had a significant effect. Additionally, the effects of the films on refrigerated skinless chicken breast meat were evaluated based on microbiological content, colour, weight loss, texture and pH. Four of the six films were examined could extend the storability of refrigerated chicken breast fillets for up to seven days. All six treated films improved the pH, colour stability, weight loss, and texture of the chicken fillets. Therefore, these findings suggested that the coatings containing sage extracts having different viscosities (2379L/220 and 2379L/221) were effective as antimicrobial adhesives in food packaging films and can be commercially applied in prolonging the storage of chicken breast meat without affecting their quality.